DEVELOPMENT OF RIGHT VIEW TO DISPEL SIXTY-TWO WRONG VIEWS - Srinonyang, Pradit (วารสารศรีล้านช้างปริทรรศน์, 2018)
The academic article “Development of Right View to Remove 62 Wrong Views” was objectively purposed to present the essence of Right View (Sammādiṭṭhi), the first constituent of the Noble Eightfold Path well-declared by the Buddha as the way leading to the extinction of sufferings. So, the Buddhists wishing to attain the extinction of defilement, which was able to assist them not to return again and again to transmigration, should tune up their views and correct their beliefs in accordance with what was directed by the Buddha.                  The study from several sources of data, especially the first source of Thai-language Tipiṭaka (Royal Edition), was found that Right View, the basis of meritorious things, should be developed to prevent wrong views from a chance to grow up. However, Right View could be incubated depending upon good companionship, and then, proper attention should be critically operated to summarize the right view. The person, after his view was rightly tuned up, should not be shaken with other different beliefs from the Buddha’s teaching. As regards, one with Right View was rightly able to accomplish the supreme goal of Buddhism, the release of sufferings.